JATARISHUN: indigenous peasant uprisings of Ecuador and Good Living - da Silva Araujo, Larissa; Reis da Silva, Ana Tereza (Caderno CRH, 2022)
This article analyzes the Indigenous Peasant Movements (IPM) of Ecuador as a social force and political actor. By proposing an alternative to the Ecuadorian crisis based on the Sumak Kawsay (Good Living) values, the IPM expand democratic spaces and formulate an extended sense of citizenship. The text focuses on the events of the 2019 national strike in Ecuador, in retrospective dialogue with previous uprisings. It draws on the testimonies of the Kayambi people, collected before and after the strike, in semi-structured interviews, and ethnographic work. Results show that the memory of previous struggles was an essential motivation for the emergence of the uprisings. Besides, unity and solidarity among rural actors and other sectors of Ecuadorian society were the basis for the strike’s strength and power. Finally, in dialogue with the Emancipatory Rural Politics, the article contributes to critical approaches to the role of indigenous peasant peoples in struggles for life alternatives.